1991
DOI: 10.1002/ijc.2910470306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of major carcinogens and alkaloids in the tobacco and mainstream smoke of ussr cigarettes

Abstract: Tobacco and mainstream smoke of USSR cigarettes were analyzed for carcinogens. The pH values of suspensions of the tobacco (5.4-5.6) and the nitrate content of the tobaccos (0.4-1.7%) were as expected for flue-cured and sun-cured tobaccos and mixtures thereof. The nicotine levels of the cigarette tobaccos (0.76-0.94%) and total alkaloid content (0.85-1.08%) were relatively low compared with tobaccos used in Western European and US cigarettes. The concentrations of tobacco-specific N-nitrosamines in the cigaret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Jenkins et al (1979aJenkins et al ( , 1979b showed that the tar, nicotine and carbon monoxide content of smoke varies between samples of a given brand of cigarettes, depending on the nation in which they are purchased. Djordjevic et al (1991) compared cigarettes from the former Union of Soviet Socialist Republics (USSR) with those from the United States and Western Europe, and found that the nicotine level and the total alkaloid content of the cigarettes from the western countries were slightly higher than in the cigarettes from the former USSR. They observed that non-filter and filter cigarettes from the former USSR had slower burning rates and yielded 14 to 16.7 puffs per cigarette, while cigarettes in the western countries yielded 11 puffs per cigarette.…”
Section: Brandmentioning
confidence: 99%
“…Jenkins et al (1979aJenkins et al ( , 1979b showed that the tar, nicotine and carbon monoxide content of smoke varies between samples of a given brand of cigarettes, depending on the nation in which they are purchased. Djordjevic et al (1991) compared cigarettes from the former Union of Soviet Socialist Republics (USSR) with those from the United States and Western Europe, and found that the nicotine level and the total alkaloid content of the cigarettes from the western countries were slightly higher than in the cigarettes from the former USSR. They observed that non-filter and filter cigarettes from the former USSR had slower burning rates and yielded 14 to 16.7 puffs per cigarette, while cigarettes in the western countries yielded 11 puffs per cigarette.…”
Section: Brandmentioning
confidence: 99%
“…The mainstream smoke generated via the smoking machine programmed with topographic smoking parameters from individual study participants was analyzed for tar, nicotine, carbon monoxide, BaP, and NNK, as described elsewhere (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Each compound of interest was assayed in triplicate in the smoke collected from the smoking of four cigarettes under parameters obtained for each participant studied.…”
Section: Mainstream Smoke Assaysmentioning
confidence: 99%
“…Therefore, a list of smoke components needs to be selected with a sufficiently broad chemical, pharmacological, and toxicological profile [ 4 ]. Hoffmann and his colleagues have published several lists with varying numbers of toxicologically and biologically active mainstream smoke components, which are well-acknowledged as Hoffmann analytes in both the tobacco industry and authorities [ 5 7 ]. In the list of Hoffmann analytes, 44 hazardous smoke components except for tar, nicotine, and carbon monoxide were divided into nine classes that are ammonia, aromatic amines, polycyclic aromatic hydrocarbons (PAH), phenols, carbonyls, hydrocyanic acid, nitrosamines, inorganic elements, and other volatile organics (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%